Parity by Comparison: The Case for Comparing Pregnant and Disabled Workers - Simon, Eliza H. (Columbia Journal of Gender and Law, 2015)
In 2008 Congress enacted amendments to the Americans With Disabilities Act (ADA) that expanded the ADA’s definition of “disability,” requiring employers to provide reasonable accommodations to workers with temporary impairments. This Article argues that the expansion of the protections of the ADA effectively expanded the protections of the Pregnancy Discrimination Act (PDA), too. As the Supreme Court recently clarified in Young v. United Parcel Service, the PDA generally requires employers to treat pregnant workers “the same as” non-pregnant workers who are similar in their ability or inability to work. Therefore, to the extent that pregnancy-related impairments mirror impairments that are accommodated by the expanded ADA, pregnant workers, too, should be entitled to reasonable accommodations. Although some scholars and courts have suggested that ADA-covered employees cannot be proper comparators for PDA plaintiffs, I make the case that these workers can, and should, be compared. First, I argue that PDA precedent requiring employers to treat pregnant workers the same as other impaired workers, as well as the legislative history of the PDA compel this comparison. Second, I draw on two theoretical approaches—intersectionality theory and “disruption” theory—to demonstrate that denying ADA comparators to PDA plaintiffs ignores the unique intersectional nature of pregnancy, and would invite stereotyping, segregation, and discrimination. In conclusion, I note that the Supreme Court itself has signaled that courts should take a more expansive view of the types of evidence that can support a PDA claim, which should include a broader approach to the comparator question.